PERSYVE - Design and validation of a questionnaire about adverse effects of antihypertensive drugs - Duarte-Silva D; Figueiras A; Herdeiro MT; Teixeira Rodrigues A; Silva Branco F; Polónia J; Figueiredo IV (Centro de Investigaciones y Publicaciones Farmaceuticas, 2014)
Objective: The aim of this study was to design and validate a questionnaire to measure perceived symptoms associated with antihypertensive drugs (PERSYVE). Methods: The PERSYVE development and validation included four stages: 1) item development (bibliographic review and questionnaire elaboration); 2) face and content validation; 3) field testing (pre-test); and 4) test-retest validation, assessment of internal consistency (Cronbach's alpha) and reproducibility over time (intraclass correlation coefficient and Cohen's kappa coefficient). Results: PERSYVE is divided into six sections according to results obtained from the literature review: (1) drug adherence, (2) perceived symptoms and how they affect quality of life (five-point Likert scale), (3) communication with health professionals, (4) perception of symptoms as adverse reactions, (5) influence on therapy compliance, and (6) adoption of non-pharmacological methods for blood pressure control. Content and face validation of the questionnaire led to some vocabulary changes and the introduction of section 2.1. Field-testing (n=26) revealed high comprehensibility of the questions. The Cronbach's alpha, calculated for section 2 (five-point Likert scale) was 0.850. PERSYVE was reproducible (n=167): kappa values presented fair to substantial reproducibility and, in section 2, ICC values resulted in good to excellent reproducibility. Conclusion: Results showed that PERSYVE is a well-structured, objective, patient-friendly, valid and reliable questionnaire. PERSYVE can be a very useful instrument in hypertensive patients' monitoring and in the screening of adverse effects.